Cell-Free DNA (cfDNA) Regulates Metabolic Remodeling, Sustaining Proliferation, Quiescence, and Migration in MDA-MB-231, a Triple-Negative Breast Carcinoma (TNBC) Cell Line - Isabel Lemos; Catarina Freitas-Dias; Ana Hipólito; José Ramalho; Fabrizio Carteni; Luís G. Gonçalves; Stefano Mazzoleni; Jacinta Serpa (Metabolites)
Background: The clinical relevance of circulating cell-free DNA (cfDNA) in oncology has gained significant attention, with its potential as a biomarker for cancer diagnosis and monitoring. However, its precise role in cancer biology and progression remains unclear. cfDNA in cancer patients’ blood has been shown to activate signaling pathways, such as those mediated by toll-like receptors (TLRs), suggesting its involvement in cancer cell adaptation to the tumor microenvironment. Methods: This impact of cfDNA released from MDA-MB-231, a triple-negative breast cancer (TNBC) cell line was assessed, focusing on glucose availability and culture duration. The impact of cfDNA on the proliferation of MDA-MB-231 cells was investigated using proliferation curves, while cellular migration was evaluated through wound healing assays. The metabolic alterations induced by distinct cfDNA variants in MDA-MB-231 cells were investigated through nuclear magnetic resonance (NMR) spectroscopy, and their effect on cisplatin resistance was evaluated using flow cytometry. Furthermore, the expression levels of DNA-sensitive Toll-like receptor 9 (TLR9) were quantified via immunofluorescence, alongside its colocalization with lysosome-associated membrane protein 1 (LAMP1). Results: This study indicates that cfDNA facilitates metabolic adaptation, particularly under metabolic stress, by modulating glucose and glutamine consumption, key pathways in tumor cell metabolism. Exposure to cfDNA induced distinct metabolic shifts, favoring energy production through oxidative phosphorylation. The anti-cancer activity of cfDNA isolated from conditioned media of cells cultured under stressful conditions is influenced by the culture duration, emphasizing the importance of adaptation and se-lection in releasing cfDNA that can drive pro-tumoral processes. Additionally, cfDNA exposure influenced cell proliferation, quiescence, and migration, processes linked to metastasis and treatment resistance. These findings underscore cfDNA as a key mediator of metabolic reprogramming and adaptive responses in cancer cells, contributing to tumor progression and therapy resistance. Furthermore, the activation of TLR9 signaling suggests a mechanistic basis for cfDNA-induced phenotypic changes. Conclusions: Overall, cfDNA serves as a crucial signaling molecule in the tumor microenvironment, orchestrating adaptive processes that enhance cancer cell survival and progression.